2018
DOI: 10.1111/jwas.12504
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Identification of Single Nucleotide Polymorphism Within the IGF‐1R Gene Associated with Growth Traits of Odontobutis potamophila

Abstract: IGF-1R plays a critical role in many physiological activities, such as development, growth, metabolism, and reproduction. Identification of genetic markers in the IGF-1R gene significantly associated with important growth traits of Odontobutis potamophila may accelerate genetic improvement. In this study, we characterized the cDNA sequence of the IGF-1R gene of O. potamophila, and our data revealed that IGF-1R contained an open reading frame of 1650 bp, encoding a polypeptide of 549 amino acids (aa). Quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Another endemic Chinese species that has attracted more recent attention is the freshwater sleeper, Odontobutis potamophila . H. Zhang, Zhang et al (), H. Zhang, Zhao et al (), and X. Zhang et al () identified and characterized single nucleotide polymorphisms (SNPs) of insulin‐like growth factor 1 receptor (IGF‐1R) genes in O. potamophila . They found that a SNP site in the intron of IGF‐1R was associated with growth performance and suggested that this SNP site could be used in marker‐assisted selection (MAS) (H. Zhang, Zhang et al ; H. Zhang, Zhao et al ; X. Zhang et al ).…”
Section: Special Issue Summarymentioning
confidence: 99%
See 4 more Smart Citations
“…Another endemic Chinese species that has attracted more recent attention is the freshwater sleeper, Odontobutis potamophila . H. Zhang, Zhang et al (), H. Zhang, Zhao et al (), and X. Zhang et al () identified and characterized single nucleotide polymorphisms (SNPs) of insulin‐like growth factor 1 receptor (IGF‐1R) genes in O. potamophila . They found that a SNP site in the intron of IGF‐1R was associated with growth performance and suggested that this SNP site could be used in marker‐assisted selection (MAS) (H. Zhang, Zhang et al ; H. Zhang, Zhao et al ; X. Zhang et al ).…”
Section: Special Issue Summarymentioning
confidence: 99%
“…H. Zhang, Zhang et al (), H. Zhang, Zhao et al (), and X. Zhang et al () identified and characterized single nucleotide polymorphisms (SNPs) of insulin‐like growth factor 1 receptor (IGF‐1R) genes in O. potamophila . They found that a SNP site in the intron of IGF‐1R was associated with growth performance and suggested that this SNP site could be used in marker‐assisted selection (MAS) (H. Zhang, Zhang et al ; H. Zhang, Zhao et al ; X. Zhang et al ). Likewise, microsatellite loci were examined for potential use in MAS in pearl oyster, Pinctada fucata martensii , which is an important commercial bivalve used for the production of marine pearls in China and Japan (Zhan et al ).…”
Section: Special Issue Summarymentioning
confidence: 99%
See 3 more Smart Citations